Analisis Penyelesaian Perselisihan Antara Pengusaha Dan Pekerja Pada PT Swakarya Indah Busana Kota Tanjungpinang - Widia Ierdiana; Fitri Nurzana; Helen Permata Sari; Mellyana Candra (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2023)
An industrial relations dispute is something that occurs between entrepreneurs and workers/laborers, as well as fellow workers in the company. Therefore, there is a need for a mechanism for resolving industrial relations disputes that can be resolved quickly, precisely, fairly and cheaply. There are several types of industrial relations according to Article 2 of Law No. 2 of 2004, including disputes over rights, interests, termination of employment relations and disputes between trade unions. This research uses a qualitative approach method in the form of analysis and understanding of meaning, between a group or a number of individuals and the subject objects being analyzed. Data collection techniques use literature study methods, whether from laws, journals, articles, literature reviews or news or information from official news websites. The results of this research want to know how the resolution of disputes between employers and workers at PT Swakarya Indah Busana resulted in an agreement between both parties, where employee salaries will temporarily be paid in full for 1 month to 263 workers and the remainder will be paid in December 2023. As well as there is supervision carried out by the Manpower Service towards PT Swakarya Indah Busana.